The Role of the Indonesian Ulama Council (MUI) in Maintaining Islamic Teachings Amid the Influence of Modern Culture - Syukur, Agus; Puspita, Ratna; Nurhadi, Nurhadi (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2025)
Modern culture and globalization cannot be avoided by world society, including Muslim society. Day by day, the world is increasingly developing towards technological progress, both in communication and information. Therefore, the influence of modern culture has two sides, namely positive and negative. Positive influence can certainly make it easier for people to access information, carry out communications, transactions, and so on. There are also many negative influences, including being able to make users of sophisticated technological devices addictive, such as gadgets or smartphones, social deviations, and transactions that are prohibited by religion. This research aims to find solutions to the negative influences caused by modern culture, then what are the tips so Muslim communities can use these modern tools with the goals and conditions recommended by religion? So with modern tools, we will create a modern culture that does not depart from the teachings of the Islamic religion. This research is included in the type of qualitative research with a descriptive approach. This research is also included in library research, and the primary data in this research is in the form of articles related to the research theme. The results of this research are that among the solutions that can be implemented by the MUI in maintaining Islamic teachings amidst the influence of modern culture are 3 ways, namely: 1) MUI to provide direction and guidance so that the Islamic community always refers to the Qur'an and Hadith as the main basis and guidelines for Islamic teachings; 2) MUI to provide direction and guidance and collaborate with the mosque council to make the mosque a center for Islamic community activities, such as Islamic culture during the time of the Prophet Muhammad, his companions, and tabi'in; 3) MUI should collaborate with the government as the authority holder to always be able to provide policies that regulate the order of life in modern Islamic society and how to monitor the success of these policies in society.